2002
DOI: 10.1159/000064359
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle within Incomplete Obliterations of Processus vaginalis Lacks Apoptotic Nuclei

Abstract: Introduction: Incomplete obliteration of processus vaginalis (PV) has been suggested to result from the persistence of smooth muscle, which should normally disappear after taking part in the descent of testis. Since apoptosis is the mechanism of disappearance, the presence or absence of apoptotic nuclei was evaluated within sacs that result from failed obliteration of PV. Materials and Methods: Twenty sacs associated with female inguinal hernia (n = 5), male inguinal hernia (n = 6), hydrocele (n = 5), hydrocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Smooth muscle cells have been found to be more frequent in sacs from inguinal hernias than from hydroceles and undescended testis in addition to insufficient apoptosis and absence of apoptotic nuclei in the smooth muscle cells from the processus vaginalis. 25 They have also been found as local thickenings around the internal ring of indirect hernias indicating inadequacy of obliteration of the processus vaginalis thereby predisposing to herniation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smooth muscle cells have been found to be more frequent in sacs from inguinal hernias than from hydroceles and undescended testis in addition to insufficient apoptosis and absence of apoptotic nuclei in the smooth muscle cells from the processus vaginalis. 25 They have also been found as local thickenings around the internal ring of indirect hernias indicating inadequacy of obliteration of the processus vaginalis thereby predisposing to herniation.…”
Section: Discussionmentioning
confidence: 99%
“…Failed apoptosis could also be related to the sympathetic nervous system which enhances smooth muscle growth and survival of smooth muscle cells in vitro. 25 Androgens indirectly regulate the descent of the testis by acting on the genitofemoral nerve possibly by releasing calcitonin gene related peptide. 26,27 In vitro studies have indicated induction of the obliteration of the processus vaginalis by transforming epithelial cells to mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently proposed that the testis descends into the scrotum through the propulsive activity of the smooth muscle content of the PV [8,9]. Inguinal hernia and hydrocele have been suggested to result from the persistence of smooth muscle, which should disappear after testicular descent [10–13]. The amount of persisting smooth muscle has been considered to determine the degree of obliteration and thus whether the clinical outcome is a hernia or hydrocele.…”
Section: Discussionmentioning
confidence: 99%
“…Inguinal/scrotal hernias are further divided into the more common indirect hernia, in which the inguinal canal is entered via the internal inguinal ring, and the direct hernia, where the hernia contents invade through a weak spot in the back wall of the inguinal canal. The formation of an inguinal/scrotal hernia is believed to be caused by the failure of the embryonic closure of the internal inguinal ring, the incomplete obliteration of the processes vaginalis (Hutson et al, 1997;Tomiyama et al, 2005), the weak triangle of the inguinal region caused by the alternated collagen subtype proportions Kral and Levine, 1995), an abnormality in the smooth muscle differentiation in the wall of the hernial sac (Tanyel et al, 1999;Tanyel et al, 2002) or from increased intra-abdominal pressure (Stoppa et al, 1987). The mode of genetic inheritance is still unclear, but hernias are likely sex-limited autosomal traits with partial penetrance .…”
Section: Inguinal/scrotal Herniamentioning
confidence: 99%
“…Inguinal/scrotal hernias, on the other hand, could be the result of the failed closure of the internal inguinal ring and the incomplete obliteration of the processes vaginalis after the testicular descent (Hutson et al, 1997;Tomiyama et al, 2005), the weak triangle of the inguinal region , an abnormality in the smooth muscle differentiation in the wall of the hernial sac (Tanyel et al, 1999;Tanyel et al, 2002), or increased intraabdominal pressure.…”
Section: Chapter 1 General Introduction General Introductionmentioning
confidence: 99%